A novel furo[3, 2-c]pyridine-based AIE photosensitizer for specific imaging and photodynamic ablation of Gram-positive bacteria. Issue 74 (30th August 2022) - Wu, Ming-Yu; Wang, Yun; Wang, Li-Juan; Wang, Jia-Li; Xia, Feng-Wei; Feng, Shun
Abstract : A novel AIE-active furo[2, 3- c ]pyridine-based photosensitizer was developed for specific imaging and photodynamic ablation of Gram-positive bacteria in vitro and in vivo . Abstract : An Rh-catalyzed tandem reaction was performed to construct an AIE-active furo[2, 3- c ]pyridine-based photosensitizer, named LIQ-TF . LIQ-TF showed near-infrared emission with high quantum yield, and high 1 O2 and ˙OH generation efficiency, and could be used for specific imaging and photodynamic ablation of Gram-positive bacteria in vitro and in vivo, showing great potential for combating multiple drug-resistant bacteria.